Murine osteoclastogenesis suppression using conditioned media produced by melanoma or activated and non‐activated Jurkat‐E6 cells. (20th February 2020) - Mambelli‐Lisboa, Nicole C.; Frare, Eduardo O.; da Costa‐Neves, Adriana; Prieto da Silva, Álvaro R. B.; Kerkis, Irina
Abstract: Conditioned medium (CM) (cell secretome) is a cocktail of growth factors, cytokines, and other soluble mediators secreted by cells into a culture medium. These growth factors are fundamental in many cellular processes such as cell growth, differentiation, and others and the composition of these factors is individual for each cell type. Osteoclasts are large multinucleated cells that are responsible for bone resorption. Immune and cancer cells are known to produce different growth factors, which are able to induce or inhibit osteoclast differentiation. Herein, we evaluated the effect of CM obtained from the supernatant of activated and non‐activated Jukart‐E6 cells, as well as from one murine (B16‐F10) and one human melanoma cell line (SKMEL28). To induce osteoclast differentiation, murine bone marrow mononuclear cells were cultured in the presence and absence of differentiation factors (DF), such as macrophage colony‐stimulating factor, prostaglandin E2, receptor activator of nuclear factor‐κB ligand, and CM. We measured the concentration of interleukin 6, tumor necrosis factor‐α and interferon γ (IFN‐γ) in CM that can inhibit or induce osteoclastogenesis. Our study demonstrated that CM obtained from each cell line suppresses or inhibits osteoclasts formation at early and intermediate stages of differentiation in the absence or presence of DF. CM obtained from activated Jurkat‐E6 cells demonstrates a stronger effect when compared with CM from naïve Jurkat‐E6 cells or human and murine melanoma cells. Moreover, CM obtained from activated Jurkat‐E6 cells shows higher secretion of IFN‐γ, which is an inhibitor of osteoclastogenesis, in comparison with CM obtained from the three other cell lines. On the other hand, CM derived from B16‐F10 cells showed a smaller inhibitory effect when compared with CM derived from the other cells.